Hydroxyapatite in oral care products—a review - Chen, L.; Al-Bayatee, S.; Khurshid, Z.; Shavandi, A.; Brunton, Paul; Ratnayake, J. (2021)
Calcium phosphate compounds form the inorganic phases of our mineralised tissues such as bone and teeth, playing an important role in hard tissue engineering and regenerative medicine. In dentistry and oral care products, hydroxyapatite (HA) is a stable and biocompatible calcium phosphate with low solubility being used for various applications such as tooth remineralisation, reduction of tooth sensitivity, oral biofilm control, and tooth whitening. Clinical data on these products is limited with varied results; additionally, the effectiveness of these apatite compounds versus fluoride, which has conventionally been used in toothpaste, has not been established. Therefore, this review critically evaluates current research on HA oral care, and discusses the role and mechanism of HA in remineralisation of both enamel and dentine and for suppressing dentine sensitivity. Furthermore, we position HA’s role in biofilm management and highlight the role of HA in dental applications by summarising the recent achievement and providing an overview of commercialised HA dental products. The review also indicates the existing limitations and provides direction for future research and commercialisation of apatite-based oral care products.